Impact of Export Diversification on Economic Growth in Sub-Saharan Africa (SSA) - (:unkn) unknown (My University, 2023)
This study investigated the impact of export diversification on the economic growth of countries in Sub-Saharan African (SSA). Trade Data are gathered from the World Integrated Trade Solution (WITS), and UN Comtrade database, using a 6-digit level range of the Standard International Trade Classification (SITC) and the Harmonised System (HS) for the Countries. Export diversification Indices data are proxies from the Herfindahl Hirschman Index (HHI) which represents the level of export product diversification for all forty-eight (48) SSA Countries between 1995 and 2020. The Panel Autoregressive Distributed Lagged Model (P-ARDL) was applied in the study. Other analysis including correlation analysis, multicollinearity, and Unit Root tests were used to achieve the objective of the study. The findings showed that export diversification has not really benefitted the SSA Countries; also, exporting raw materials and other primary products does not benefit the region, and therefore, the countries should continue leveraging on the potential of diversifying their exports and exploring sectors such as the manufacturing to attain more economic gains. To achieve export gains, oil/minerals products should be exported as finished products, not as raw materials, especially, from those nations that are resources endowed. These raw materials should be best used domestically to aid production into finished/refined products for subsequent exports.
Keywords: African Research